Statin Therapy Is Associated With Improved Pathologic Response to Neoadjuvant Chemoradiation in Rectal Cancer - Mace, Adam G.; Gantt, Gerald A.; Skacel, Marek; Pai, Rish; Hammel, Jeff P.; Kalady, Matthew F. (Diseases of the colon & rectum, 2013)
BACKGROUND:Achieving a pathologic complete response to neoadjuvant chemoradiation improves prognosis in rectal cancer. Statin therapy has been shown to enhance the impact of treatment in several malignancies, but little is known regarding the impact on rectal cancer response to neoadjuvant chemoradiation. OBJECTIVE:The purpose of this study was to determine whether statin use during neoadjuvant chemoradiation improves pathologic response in rectal cancer. DESIGN:This was a retrospective cohort study based on data from a prospectively maintained colorectal cancer database. The 2 cohorts were defined by statin use during neoadjuvant chemoradiation. SETTING:This study was performed at a single tertiary referral center. PATIENTS:Four hundred seven patients with primary rectal adenocarcinoma who underwent neoadjuvant therapy then proctectomy between 2000 and 2012 were included. Ninety-nine patients (24.3%) took a statin throughout the entire course of neoadjuvant therapy. MAIN OUTCOME MEASURES:The primary outcome measure was pathologic response to neoadjuvant chemoradiotherapy as defined by the American Joint Committee on Cancer tumor regression grading system, grades 0 to 3. RESULTS:Patients in the statin cohort had a lower median regression grade (1 vs 2, p = 0.01) and were more likely to have a better response (grades 0–1 vs 2–3) than those not taking a statin (65.7% vs 48.7%, p = 0.004). Statin use remained a significant predictor of an American Joint Committee on Cancer grade 0 to 1 (OR, 2.25; 95% CI, 1.33–3.82) in multivariate analyses. Although statin use itself did not significantly improve oncologic outcomes, an American Joint Committee on Cancer grade 0 to 1 response was associated with statistically significant improvements in overall survival, disease-free survival, cancer-specific mortality, and local recurrence. LIMITATIONS:This was a retrospective study and subject to nonrandomization of patients and incorporated patients on variable statin agents and doses. CONCLUSIONS:Statin therapy is associated with an improved response of rectal cancer to neoadjuvant chemoradiation. These data provide the foundation for a prospective clinical trial.